1977
DOI: 10.1172/jci108613
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide production and reducing activity in human platelets.

Abstract: A B S T R A C T Human platelets contain the cuprozinc (cytoplasmic) and manganese (mitochondrial) forms of superoxide dismutase. Nevertheless, superoxide radicals were detectable in the surrounding medium of metabolically viable platelet suspensions by using two assay systems: cytochrome c and nitroblue tetrazolium. The quantity of superoxide generated by platelets (5 x 105 superoxide radicals/platelet per 10 min) was constant and did not increase after aggregation by agents such as collagen and thrombin. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
5

Year Published

1981
1981
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 43 publications
3
76
1
5
Order By: Relevance
“…However, fluoride is not believed to activate adenylate cyclase in intact cells (Vigdahl et al, 1969). In leucocytes (Curnutte & Babior, 1975) and in platelets (Marcus et al, 1977) fluoride causes production of superoxide, which may activate platelets in synergism with other inducers, but such secondary activation is unlikely to be the main mechanism of fluoride-induced secretion. One might postulate that fluoride could act via an activation of the production of thromboxane A2; but no malonaldehyde production (E. H. Miirer & M. H. Fukami, unpublished work) or 02 burst (Miirer, 1968) accompanies fluoride-induced secretion, which argues against this suggestion.…”
Section: Statistical Treatment Ofresults Inmentioning
confidence: 99%
“…However, fluoride is not believed to activate adenylate cyclase in intact cells (Vigdahl et al, 1969). In leucocytes (Curnutte & Babior, 1975) and in platelets (Marcus et al, 1977) fluoride causes production of superoxide, which may activate platelets in synergism with other inducers, but such secondary activation is unlikely to be the main mechanism of fluoride-induced secretion. One might postulate that fluoride could act via an activation of the production of thromboxane A2; but no malonaldehyde production (E. H. Miirer & M. H. Fukami, unpublished work) or 02 burst (Miirer, 1968) accompanies fluoride-induced secretion, which argues against this suggestion.…”
Section: Statistical Treatment Ofresults Inmentioning
confidence: 99%
“…Gutteridge and co-workers (24) demonstrated that Al 3+ salts do not directly stimulate lipid peroxidation, but instead accelerate iron-and hydrogen peroxide-dependent lipid peroxidation in phospholipid liposomes and human erythrocyte membranes. On the other hand, superoxide and hydrogen peroxide are known to induce platelet aggregation and they can be produced by these cells (8). Although Al 3+ has no redox capacity, the metal can cause alterations at the membrane level facilitating iron-initiated lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The end products of lipid peroxidation are cytotoxic and may cause platelet dysfunction. Nevertheless, reactive oxygen species (ROS) such as the superoxide anion, hydrogen peroxide and the hydroxyl radical, well-known stimulators of lipid peroxidation, are generated by platelets (7,8). These species have been shown to be modulators of platelet adhesion and aggregation, directly or through effects on vascular endothelial cells which generate prostacyclin and nitric oxide (9).…”
Section: Introductionmentioning
confidence: 99%
“…Since catalase did not affect the activity of NO or of EDRF, it is likely that superoxide anions (02), rather than another oxygen-derived radical, play a role in the destruction of these compounds (Gryglewski et al, 1986b). Superoxide anions are present in the medium of platelet suspensions (Marcus et al, 1977), although the amount of 02-present does not increase during aggregation and SOD does not affect platelet function directly (Marcus et al, 1977;Clemmons et al, 1985). These findings suggest that although 2-are not involved in platelet aggregation per se they may contribute to the inactivation of NO.…”
Section: Discussionmentioning
confidence: 99%